Two Sides of the Same Coin: TFIIH Complexes in Transcription and DNA Repair - Alexander Zhovmer; Valentyn Oksenych; Frédéric Coin (The Scientific World Journal)
TFIIH is organized into a seven-subunit core associated with a three-subunit Cdk-activating kinase (CAK) module. TFIIH has roles in both transcription initiation and DNA repair. During the last 15 years, several studies have been conducted to identify the composition of the TFIIH complex involved in DNA repair. Recently, a new technique combining chromatin immunoprecipitation and western blotting resolved the hidden nature of the TFIIH complex participating in DNA repair. Following the recruitment of TFIIH to the damaged site, the CAK module is released from the core TFIIH, and the core subsequently associates with DNA repair factors. The release of the CAK is specifically driven by the recruitment of the DNA repair factor XPA and is required to promote the incision/excision of the damaged DNA. Once the DNA lesions have been repaired, the CAK module returns to the core TFIIH on the chromatin, together with the release of the repair factors. These data highlight the dynamic composition of a fundamental cellular factor that adapts its subunit composition to the cell needs.